Evolving landscapes in multiple sclerosis research: adaptive designs and novel endpoints. Issue 1 (December 2016) - Beelke, Manolo; Antonini, Paola; Murphy, Michael
Abstract The increasing amount of highly effective treatment options in relapsing forms of multiple sclerosis (MS) requires innovative clinical trial design strategies. These strategies may encompass the application of adaptive designs as well as the adoption of innovative primary outcome measurements. The offered advantages would include, among others, shorter study follow-up periods and reduction in the number of patients either on placebo or on non-suitable dosages of the small molecules or biological products under examination. Changing the primary endpoint during the study conduct additionally represents an option, when the primary endpoint originally is either a composite endpoint of Magnetic Resonance Imaging (MRI) and clinical variables or a unitary endpoint of clinical variables. The new outcome measurement of no-evidence-of-disease activity (NEDA) – the former disease activity free (DAF) status, might represent an attractive approach and NEDA may become a new standard for clinical trials in relapsing MS (RMS), particularly for pivotal Phase III trials, though also earlier phase trials and exploratory clinical research might benefit from this endpoint. Future studies in RMS could incorporate NEDA as a primary endpoint and utilize the adaptive design methodology in order to reduce the sample size and the duration of new therapeutic agents' clinical development.